Design aspects of the combined medicinal product with multifunctional action based on herbal drugs - S. A. Kotov; T. M. Gontova; A. G. Kotov (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Combined herbal medicines for the treatment and prevention of allergic diseases are perspective substitutes for the «classic» drugs of H-1 receptor blockers of the 1st and 2nd generation. Literary-logical methods are quite effectively used for scientifically justified design of these drugs, namely phytopharmacological drug design (PPD) and phytochemical drug design (PCD). The aim of the work - the search for ways of the scientifically justified design of a combined multifunctional medicine based on the bur-marigold, which normalizes the functioning of the body's defence systems, increases the body's nonspecific resistance, normalizes the immune status using literary-logical and statistical methods of analysis. The design of the preparation was carried out using literature data for PPD and experimental and literature data for PCD. Statistical processing method - Spearman's rank correlation coefficient was used. Design aspects of the combined herbal medicine, which includes a bur-marigold herb, calendula flowers, hawthorn leaves and flowers were considered using of a system-comparative analysis of information and its processing by the method of the Spearman's rank correlation coefficient determination. When PCD development of various combinations of herbal drugs, information about the content of such biologically active substances (BAS) as flavonoids, oxycinnamic acids, polyphenols, triterpenes, proteins/amino acids, polysaccharides was used. When PPD development the spectra of pharmacological activity were determined and a quantitative assessment to them in the system of marks for each of the herbal drug of the combined medicine was given. The PCD and PPD data into the matrix for calculating the Spearman rank correlation coefficient of the «action-sum of BAS» was entered. As a result, a strong, direct and statistically significant correlation relation (p from 0.924 to 0.997) between the content of oxycinnamic acids, polyphenols, triterpenes, proteins/amino acids, polysaccharides and such pharmacological actions as capillary-strengthening, anti-inflammatory, immunostimulating; choleretic, hepatoprotective, improving metabolism; diuretic, hypotensive, sedative, tonic, desensitizing, antipruritic, reparative for the studied herbal combinations was found. The obtained results of the PCD and PPD development as well as the study of the correlation «action-sum of BAS» by calculating the Spearman's rank correlation coefficient, this suggests the developed combined herbal medicinal product with multifunctional action is perspective in the complex therapy of allergic diseases accompanied by a decrease in the body's resistance and immunostatus.